Role of lysine residues of the Magnaporthe oryzae effector AvrPiz‐t in effector‐ and PAMP‐triggered immunity. (8th February 2019) - Bai, Pengfei; Park, Chan‐Ho; Shirsekar, Gautam; Songkumarn, Pattavipha; Bellizzi, Maria; Wang, Guo‐Liang
Summary: Magnaporthe oryzae is an important fungal pathogen of both rice and wheat. However, how M. oryzae effectors modulate plant immunity is not fully understood. Previous studies have shown that the M. oryzae effector AvrPiz‐t targets the host ubiquitin‐proteasome system to manipulate plant defence. In return, two rice ubiquitin E3 ligases, APIP6 and APIP10, ubiquitinate AvrPiz‐t for degradation. To determine how lysine residues contribute to the stability and function of AvrPiz‐t, we generated double (K1, 2R‐AvrPiz‐t), triple (K1, 2, 3R‐AvrPiz‐t) and l ysine‐ f ree (LF‐AvrPiz‐t) mutants by mutating lysines into arginines in AvrPiz‐t. LF‐AvrPiz‐t showed the highest protein accumulation when transiently expressed in rice protoplasts. When co‐expressed with APIP10 in Nicotiana benthamiana, LF‐AvrPiz‐t was more stable than AvrPiz‐t and was less able to degrade APIP10. The avirulence of LF‐AvrPiz‐t on Piz‐t:HA plants was less than that of AvrPiz‐t, which led to resistance reduction and lower accumulation of the Piz‐t:HA protein after inoculation with the LF‐AvrPiz‐t ‐carrying isolate. Chitin‐ and flg22‐induced production of reactive oxygen species (ROS) was higher in LF‐AvrPiz‐t than in AvrPiz‐t transgenic plants. In addition, LF‐AvrPiz‐t transgenic plants were less susceptible than AvrPiz‐t transgenic plants to a virulent isolate. Furthermore, both AvrPiz‐t and LF‐AvrPiz‐t interacted with OsRac1, but the suppression of OsRac1‐mediated ROS generation by LF‐AvrPiz‐t was significantly lower than that by AvrPiz‐t. Together, these results suggest that the lysine residues of AvrPiz‐t are required for its avirulence and virulence functions in rice.